First treatment activity and outcome of radioiodine therapy in thyroid cancer patients with metastases in lymph nodes: mathematical correlation and clinical implica - Kozak, O.V.; Мuzichenko, L.V.; Trembach, A.M.; Voit, N.U.; Turicina, V.V. (Experimental Oncology, 2006)
Aim: The aim of the work was to estimate the strength of influence of the first 131I activity on the outcome of the first course of radioiodine treatment as compared with other variables such as remnants volume, size and number of metastases in lymph nodes. Patients and Methods: 68 adult patients with differentiated thyroid cancer have been treated with radioiodine after thyroidectomy. All patients had metastatic lesions in lymph nodes accumulating 131I. Activities administered amounted from 1000 to 6000 MBq. From 1 to 4 courses of radioiodine therapy were necessary for total ablation of metastases and remnants. Logistic function has been used to describe the probability of the total ablation of metastases and thyroid remnants after the first course. Results: It was shown that the value of the first activity has the decisive influence on the treatment outcome. In patients included into analysis the outcome of the first course actually does not depend on level of radioiodine accumulation in pathological lymph nodes and effective half-time of 131I excretion in remnants. Conclusion: As a result, in the case of metastatic lesions in lymph nodes accumulating radioiodine the first activity should not be less then 5000 MBq with the aim of minimizing the number of courses. Outcome of the treatment only slightly depends on such factors as histology, the number and the size of metastases in lymph nodes. Цель: оценить влияние первой лечебной активности 131I на результат радиойодотерапии по сравнению с размерами
остаточной ткани щитовидной железы, количеством и размерами метастазов в лимфоузлах. Материалы и методы:
68 больным с дифференцированным раком щитовидной железы проводили лечение радиойодом после тиреоидэктомии. У
всех пациентов было выявлено патологическое накопление 131I в пораженных лимфоузлах. Введенные активности принимали
значение от 1000 до 6000 МБк. Для полного уничтожения тиреоидной ткани, включая метастатические очаги поражения,
необходимо было провести от 1 до 4 курсов радиойодотерапии. Для оценки вероятности полного уничтожения метастазов
и остаточной ткани после первого курса радиойодотерапии была выбрана логистическая функция. Результаты: результат
применения I курса радиойодотерапии не зависит от уровня накопления 131I в лимфоузлах, а также от эффективного периода
полувыведения радиойода из остаточной ткани щитовидной железы. Выводы: у больных с дифференцированным раком
щитовидной железы в случае наличия пораженных лимфоузлов, в которых накапливается радиойод, первая лечебная
активность не должна быть меньше 5000 МБк — для уменьшения количества курсов радиойодотерапии до минимума.
Результат применения радиойодотерапии слабо зависит от таки